Tara Apartment: A Thoughtful Approach to Present –Day Housing - Sushama S. Dhepe; Sanjay N. Kumbhare (Theory and Applications of Engineering Research Vol. 1, 2023)
Tara Apartment designed by Charles Correa is a unique piece of housing design. It is relevant answer to today’s housing challenges such as social community, interactivity, security, and vantage. The social aspects of housing in regards to Tara Apartment, which are essential in current housing buildings, have been addressed in this chapter. Through graphical analysis the design challenges of the Tara Apartment with respect to present day aspects of housing are presented in the chapter.